Sulphur dioxide adsorption on the Ni(110) surface - Zebisch, P.; Weinelt, M.; Steinrück, Hans-Peter (Surface Science, 1993)
The adsorption of SO on Ni(110) has been studied in detail by temperature programmed desorption (TPD), low energy electron diffraction (LEED), X-ray photoelectron spectroscopy (XPS), and angle resolved UV photoelectron spectroscopy (ARUPS) using linearly polarized synchrotron radiation. At 100 K SO is found to chemisorb in molecular form on Ni(110) with a saturation coverage of 0.5 ML (1 ML = 1 molecule Ni-atom). The saturated chemisorbed layer exhibits a c(2 × 2) LEED pattern. At initial coverages below 0.25 ML, SO completely decomposes upon heating to 750 K; for higher coverages molecular SO desorption is also observed in a single peak between 300 and 400 K. From the angle resolved UPS spectra and symmetry selection rules we deduce the symmetry of the adsorbed SO molecules for low coverages as C (σ), with the molecular O-S-O plane oriented perpendicular to the surface and aligned along the [001] azimuth (perpendicular to the close-packed substrate rows). Within the plane the molecule is tilted, which is attributed to an additional Ni-O interaction. In the saturated layer the symmetry is further reduced to C indicating an additional tilting and/or rotation of the molecular plane with respect to the substrate. © 1993.